2018
DOI: 10.1007/s11894-018-0607-z
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Esophagitis in Children: Endoscopic Findings at Diagnosis and Post-intervention

Abstract: Gold standard of diagnosis and assessment of response to therapy in EoE requires multiple endoscopies with biopsies for histology, which allows for observation of the esophageal mucosa. Typical endoscopic findings in patients with EoE include edema, exudate, furrowing, concentric rings, and strictures. Endoscopic findings have been broadly characterized into inflammatory features (edema, exudate, furrowing) and fibro-stenotic features (rings, stricture), in order to better reflect their underlying pathophysiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 31 publications
2
20
1
1
Order By: Relevance
“…In the presented cohort of patients, white exudates and furrows were the 2 most typical endoscopic findings. This result are similar to those of a recent review of endoscopic findings that analysed almost 2,000 children and adolescents with newly-diagnosed EoE [15]. In addition, one of the most important papers on EoE, a meta-analysis of more than 100 studies of both children and adults with EoE, (Kim et al, 2012) reported that there were significant differences between children and adults.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the presented cohort of patients, white exudates and furrows were the 2 most typical endoscopic findings. This result are similar to those of a recent review of endoscopic findings that analysed almost 2,000 children and adolescents with newly-diagnosed EoE [15]. In addition, one of the most important papers on EoE, a meta-analysis of more than 100 studies of both children and adults with EoE, (Kim et al, 2012) reported that there were significant differences between children and adults.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, 27.6% of all the children had visually normal oesophageal mucosa at the time of EoE diagnosis. Bolton et al found that between 10% -33% of children with EoE presented with a macroscopically normal oesophagus [15]. In the current study, no differences were observe in this subgroup in terms of clinical symptoms, or in the density of eosinophilic infiltration.…”
Section: Discussioncontrasting
confidence: 64%
“…The pattern of abnormality varies between patients [ 7 ], and each sign may occur in isolation or in combination. Typical endoscopic findings in patients with EoE include edema, exudates, furrowing, concentric rings, and strictures [ 9 ]. In our study, the most common endoscopic features were furrowing (82.9%), edema (74.3%), rings (47.5%), and exudates (22.9%).…”
Section: Discussionmentioning
confidence: 99%
“…About 10%-33% of children diagnosed with EoE have normal esophageal mucosa with common endoscopic findings of adults, such as esophageal rarely observed in children. Consequently, in children, the valuable features of adult endoscopy alone do not make a reliable diagnosis of EoE or assess disease activity, and adult-like scoring is less important in diagnosing or evaluating response to treatment (20,21). Recent studies suggested that ultrasound can be used for examining esophageal diseases, such as GERD-caused esophagitis.…”
Section: Discussionmentioning
confidence: 99%